2014
DOI: 10.7567/jjap.53.112701
|View full text |Cite
|
Sign up to set email alerts
|

F2-laser-induced micro/nanostructuring and surface modification of iron thin film to realize hydrophobic and corrosion resistant

Abstract: Nanoswellings of 60 nm height and 500 nm diameter on average of an iron thin film deposited on a silica glass substrate at regular intervals of 2.5 µm were fabricated by the irradiation of a 157 nm F2 laser. The F2 laser was focused on the iron thin film by each microsphere made of silica glass of 2.5 µm diameter, which covered the entire surface of the films. The surface of the silica glass substrate underneath the F2-laser-irradiated iron thin film selectively swelled to push up the film. After the laser-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…8,9) For the microstructuring, we used microspheres made of silica glass of 2.5 µm diameter, which covered the entire surface of the sample during laser irradiation. 10,11) In the present work, we observed the fabricated microstructure and contact angle of water on the laserirradiated silicone rubber. Moreover, the microstructured silicone rubber was immersed in water to see how the air gap layer can be formed between silicone and water.…”
mentioning
confidence: 89%
“…8,9) For the microstructuring, we used microspheres made of silica glass of 2.5 µm diameter, which covered the entire surface of the sample during laser irradiation. 10,11) In the present work, we observed the fabricated microstructure and contact angle of water on the laserirradiated silicone rubber. Moreover, the microstructured silicone rubber was immersed in water to see how the air gap layer can be formed between silicone and water.…”
mentioning
confidence: 89%
“…The dispersed solution was dripped on the surface of the Al-coated silicone rubber. Thus, a single layer of microspheres was formed on the Al-coated silicone rubber, in addition to the removal of excess microspheres [21,22].…”
Section: Methodsmentioning
confidence: 99%
“…When an ArF excimer laser of 193 nm wavelength irradiates the surface of the silicone rubber, the main chain of Si–O bonds of silicone undergoes photodissociation into smaller molecules, resulting in the swelling of the laser-irradiated area [16,17,18,19,20]. For the micro/nanostructuring, microspheres made of silica glass, 2.5 μm in diameter, were used [21,22]. Very recently, we also found that the subsequent formation of a textured nanometer-sized Al thin film resulted in the addition of a nanostructuring effect to the microstructured silicone.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, as another approach to obtain a superhydrophobic property using laser, we used our previous photochemical processing of silicone rubber to fabricate the microstructure on the surface; when a 193-nm ArF excimer laser irradiated the surface of silicone rubber, only the main chain of Si-O bonds of silicone could be photodissociated into the lower molecules, resulting in the swelling of the laser-irradiated area [15][16][17][18][19]. For the microstructuring, we used microspheres made of silica glass of 2.5 μm diameter, which covered the entire surface of sample during laser irradiation [14,20]. Very recently, we also found that the subsequent formation of a 50-nm-thick, textured Al thin film resulted in adding a nanostructuring effect to the microstructured silicone, showing a highly superhydrophobic property [21].…”
Section: Introductionmentioning
confidence: 99%